2018
DOI: 10.1101/364018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic screening for mutants with altered seminal root numbers in hexaploid wheat using a high-throughput root phenotyping platform

Abstract: The root is the main channel for water and nutrient uptake in crops. Optimisation of root architecture provides a viable strategy to improve nutrient and water uptake efficiency and maintain crop productivity under water-limiting, nutrient-poor conditions. We know little, however, about the genetic control of root development in wheat, a crop supplying 20% of global calorie and protein intake. To improve our understanding of the genetic control of root development in wheat, we conducted a high-throughput scree… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This ‘hidden half’ of plants is a conduit for resource uptake from the soil, and logically a high‐value target for manipulation to improve crop productivity on nutrient‐deficient soils (Meister et al., 2014). Besides anchorage, storage functions, synthesis and accumulation of secondary metabolites, root systems serve as an interface for symbiotic microbial relationships (Khan et al., 2016; Shorinola et al., 2019). Roots are becoming a key target for a second green revolution, and are deemed essential for production of high‐yielding food grains such as wheat and rice (Gewin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This ‘hidden half’ of plants is a conduit for resource uptake from the soil, and logically a high‐value target for manipulation to improve crop productivity on nutrient‐deficient soils (Meister et al., 2014). Besides anchorage, storage functions, synthesis and accumulation of secondary metabolites, root systems serve as an interface for symbiotic microbial relationships (Khan et al., 2016; Shorinola et al., 2019). Roots are becoming a key target for a second green revolution, and are deemed essential for production of high‐yielding food grains such as wheat and rice (Gewin, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As the root develops, some of the peripheral elements can increase in size becoming similar to the initial CMX. In recent years, several studies on root system architecture uncovered the genetic basis of these traits, however, most studies focused on the geometric traits, such as root number, length, diameter and, angle (Christopher et al, 2013; Golan et al, 2018; Hamada et al, 2012; Shorinola et al, 2019; Soriano & Alvaro, 2019; Voss‐Fels, Snowdon, & Hickey, 2018). On the other hand, root anatomical traits were less studied and remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the "hidden half" in polyploid wheats The "hidden half" of wheat, referring to the root system, plays fundamental roles in ensuring nutrient and water uptake efficiency, and thus the adaptability of wheat to diverse growth environments. High-throughput screening of mutant populations, genetic mapping studies, and gene transcriptome profiling have found multiple mutants with altered root architecture, QTLs for wheat root traits, and candidate genes and signaling pathways relating to root development (An et al, 2006;He et al, 2014;Shorinola et al, 2019;Zhuang et al, 2021). These QTLs/genes tend to be related to plant hormone (BR, AUX, and cytokinin) signaling and ROS homeostasis (He et al, 2014;Zhuang et al, 2021).…”
Section: Adaptation To Environmental Constraintsmentioning
confidence: 99%